Vigo: Ciudad serpiente. Ciudad del corazón - Mejía Ruiz, Carmen (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2010)
In this paper we analyse the image of Vigo that Fran Alonso transmits in his work, both in the poetry book Cidades as well as in the stories book Cemiterio de elefantes. Fran Alonso’s image of Vigo is, at the same time, real and magical, diurnal and nocturne, full of personal anecdotes and of the little stories lived by the characters in his books.
Keywords: Vigo; Fran Alonso; Cidades; Cemiterio de elefantes